Myocardial revascularization surgery: hospitalization characteristics and changes related to hospitalization time - Cintia Koerich; Gabriela Marcellino de Melo Lanzoni; Giovana Dorneles Callegaro Higashi; Alacoque Lorenzini Erdmann; Betina Hörner Schlindwein Meirelles; Maria Aparecida Baggio (Universidade Federal de Goias, 2017)
The study objective was to identify the hospitalization characteristics and changes presented by individuals submitted to Myocardial Revascularization Surgery and its association with hospitalization time for the surgery. We conducted a cross-sectional observational and epidemiological study, between March of 2013 and March of 2014, with 99 individuals submitted to Myocardial Revascularization Surgery. We verified chest pain and angina/thoracic pain pre-surgery and respiratory insufficiency, hypertermia, hypertension and arrythmias post-surgery as predictors for a longer hospital stay. The association between hospitalization characteristics and clinical changes with hospitalization time of individuals submitted to Myocardial Revascularization Surgery provides subsidies for nurses, all health professionals, and managers, to create early detection strategies for complications related to Myocardial Revascularization Surgery.